Bancada de linearização para amplificadores de potência destinados a sistemas 5G - Martins, João Filipe da Silva (2021)
The present work deals with digital pre-distortion for linearization of nonlinear systems. In this work a linearization bench will be built for fifth generation (5G) systems applied to a 28GHz power amplifier. For this, some aspects related to the 5G mobile network are initially presented, as well as several figures of merit widely used in the characterization of power amplifiers. After familiarizing with the previous topics, behavioral modeling techniques in baseband using memory models (MP) are discussed. Finally, some digital pre-distortion (DPD) techniques are presented, comparing the DPD methods by indirect and direct learning. The work is complemented with the application of the chosen method (DPD by indirect learning) in a laboratory environment. A linearization bench is implemented with the purpose of linearizing the amplifier under study. Finally, results are collected and discussed, verifying that the solution chosen for the amplifier linearization, despite having a satisfactory performance, is not the best answer to the problem, and other solutions based on different DPD techniques may present better results.